Interpretation of the Meaning in the Poem "Gerimis Jatuh" by Sapardi Djoko Damono: A Semiotic Analysis of Roland Barthes - Salwa Yumna Soyu (Research in Education, Technology, and Multiculture, 2023)
Abstract: Semiotics is the study of signs. With this science, one can understand the meaning contained in the signs that appear in a work of literature and art. In studying a sign, semiotic approaches are needed, one of which is the approach proposed by Roland Barthes. To apply Roland Barthes' approach to a literary work of poetry, the author chose a poem by Supardi Djoko Damono entitled "Gerimis Jatuh". The type of research used is semiotic research with data collection methods in the form of literature and note-taking techniques. The methods and techniques of data analysis used are descriptive analysis methods associated with Roland Barthes' theory. The results of this study show that the poem "Gerimis Jatuh" is an expression of the author's feelings of sorrow for someone he misses.    Keywords: semiotics, Roland Barthes, poetry, gerimis jatuh